2003
DOI: 10.1023/a:1025467600662
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to determine whether measurement of salivary/sputum pepsin could be used as a surrogate marker for detecting gastroesophageal reflux using 24-hr esophageal pH monitoring as the gold standard. Patients with gastroesophageal reflux symptoms underwent simultaneous 24-hr esophageal pH monitoring and collection of saliva and sputum samples for pepsin measurement using a recently developed assay. In all, 16 patients provided 19 positive (10.6%) and 161 negative pepsin assays. The mean p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(24 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…In keeping with our findings, pepsin detection in throat sputum has been suggested to be a sensitive and non-invasive diagnostic method for laryngopharyngeal reflux [20]. Our study supports previous studies on the identification of pepsin in airway secretions for the diagnosis of laryngopharyngeal reflux [26,27,28,29]. Pepsin was detected mainly in the samples collected at the time of symptoms (n = 18).…”
Section: Discussionsupporting
confidence: 91%
“…In keeping with our findings, pepsin detection in throat sputum has been suggested to be a sensitive and non-invasive diagnostic method for laryngopharyngeal reflux [20]. Our study supports previous studies on the identification of pepsin in airway secretions for the diagnosis of laryngopharyngeal reflux [26,27,28,29]. Pepsin was detected mainly in the samples collected at the time of symptoms (n = 18).…”
Section: Discussionsupporting
confidence: 91%
“…Using esophagitis as the gold standard, they found that the sensitivity of pepsin was 83% 6 . In another study of sputum samples in adults with GER symptoms undergoing pH monitoring, Potluri et al report that the sensitivity of pepsin in sputum at any given time, using a pH drop to <4 as the gold standard reflux test, was 75% and specificity 91% for proximal acid reflux while it had a sensitivity of 63% and a specificity of 92% for distal acid reflux 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In limited previous studies, pepsin, which is produced in the stomach, has been found in the lungs of children and adults with respiratory disease suggesting the presence of microaspiration of gastric contents, but there has been an inconsistent relationship with lung pepsin and reflux monitoring 2–7 . In a single adult study in which pH measurements were used, the sensitivity of salivary pepsin in predicting proximal esophageal reflux was 75% and the specificity was 91% 7 . In a single pediatric study of children with reflux symptoms and respiratory disease, the authors found 84% of patients with respiratory disease and reflux symptoms were pepsin positive.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchoscopy is an invasive diagnostic procedure, therefore alternative methods to measure pepsin are sought. Salivary pepsin seems an attractive option because of ease of sampling, but no pediatric studies have been performed so far with comparison with pH-MII 13–16 . The objective of this study is to test the sensitivity of salivary pepsin for diagnosing reflux-related lung disease, compared against combined pH-MII testing, endoscopy, and GERD symptom scores.…”
mentioning
confidence: 99%